ABC–ABC‐Type Directly meso–meso Linked Porphyrin Dimers. Issue 2 (18th December 2018) - Higashino, Tomohiro; Kurumisawa, Yuma; Iiyama, Hitomi; Imahori, Hiroshi
Abstract: Covalently linked porphyrin oligomers are attractive because of their extended π‐conjugated systems. Among various porphyrin oligomers, directly meso – meso linked porphyrin oligomers exhibit unique photophysical properties due to their strong exciton couplings derived from the alternative orthogonal geometry of the porphyrins. Although their structural and electronic properties can be greatly altered by substituents at meso positions, it is still difficult to introduce different substituents at the meso positions. Thus, it is a challenge to develop general synthetic methodologies for functional porphyrin dimers and oligomers with different substituents at the meso positions. Herein, a general synthetic strategy for ABC–ABC‐type directly meso – meso linked porphyrin dimers by stepwise functionalization starting from 10, 15, 20‐ meso ‐free 5‐substituted porphyrin as building block is established. A meso ‐ABC–ABC‐type meso – meso ‐linked donor–π‐acceptor‐type porphyrin dimer was prepared and exhibited the highest power conversion efficiency (7.91 %) ever reported for dye‐sensitized solar cells based on dimeric orthogonal donor–π‐acceptor‐type organic sensitizers. This synthetic strategy will provide useful guidance for the rational design of functional porphyrin dimers and oligomers for diverse applications. Abstract : A general synthetic strategy for ABC‐ABC‐type directly meso – meso linked porphyrin dimers (see figure) by stepwise functionalization was established. An ABC–ABC‐type meso – meso ‐linked porphyrin dimer exhibited the highest power conversion efficiency ever reported for dye‐sensitized solar cells with orthogonal dimeric donor–π‐acceptor‐type organic sensitizers.